The Formation of Nanoscale Closed Graphene Surfaces during Fullerite C60 Hot Isostatic Pressing - Danil V. Sivkov; Olga V. Petrova; Sergey V. Nekipelov; Alexander S. Vinogradov; Roman N. Skandakov; Ksenia A. Bakina; Sergey I. Isaenko; Anatoly M. Ob’edkov; Boris S. Kaverin; Viktor N. Sivkov (Applied Sciences, 2021)
The fullerite C60 modified by hot isostatic pressing (HIP) at 0.1 GPa in argon near and beyond its thermal stability region (920–1270 K temperature interval) was studied by X-ray diffractometry, Raman spectroscopy, ultra soft X-ray photoelectron and near edge X-ray absorption fine structure spectroscopy. It was found that the C60 molecules merge into closed nanocapsules with a graphene surface during the thermal treatment. The conducted studies showed that using HIP treatment of the fullerite C60, it is possible to obtain a chemically resistant material with a high hardness and elasticity, as well as a density lower than that of the graphite. This new material, consisting of closed graphene nanocapsules 2–5 nm in size, formed by sp2 covalent bonds between carbon atoms is promising for various applications, and as a basis for the synthesis of new composite materials.